Superior oblique tendon (Brown’s) syndrome as the presenting finding in childhood onset HLA-B27-related enthesitis and juvenile idiopathic oligoarticular arthritis - Pham, C.; Utz, V.; Marcotty, A.; Zeft, A.; Rychwalski, P. (Reumatismo, 2014)
We report two patients who presented with Brown’s syndrome. The first is a 7-year-old boy who at the time of his diagnosis was also found to have enthesitis and HLA-B27 positivity. The second patient was diagnosed with bilateral Brown’s syndrome at 13 months of age. At age 7 she developed a persistent oligoarticular arthritis and unilateral anterior iritis consistent with the oligoarticular Juvenile Idiopatic Arthritis (JIA) phenotype. These cases highlight ophthalmologic findings and diagnostic considerations with respect to Brown’s syndrome and associated childhood onset rheumatologic disease.